Real-time Microscope-integrated Optical Coherence Tomography-guided Stromal Fluid Drainage in Corneal Hydrops for Early Resolution of Corneal Edema - Pranita Sahay; Rinky Agarwal; Prafulla Kumar Maharana (Delhi Journal of Ophthalmology)
Aim: This study aims to describe a novel technique of microscope-integrated optical coherence tomography (MiOCT)-guided stromal fluid drainage in corneal hydrops with multiple stromal fluid clefts for rapid resolution. Materials and Methods: Eight patients of keratoconus with corneal hydrops with multiple stromal fluid clefts underwent this procedure. Medical management was initiated in all cases at presentation and intervention was performed only in cases with poor response to medical therapy at 3 weeks. The surgical technique comprised of MiOCT-guided localization of the stromal fluid clefts followed by multiple venting incisions into the stromal fluid clefts with micro-vitreoretinal blade and simultaneous air tamponade in the anterior chamber. Corneal massage with Merocel sponge further aided in draining and imbibing fluid through the incision site. Time taken for resolution of corneal edema, requirement for repeat procedure and any complication arising out of this procedure was noted. Results: Eight patients of acute corneal hydrops (5–30 years) underwent this procedure. The primary diagnosis was bilateral keratoconus for all. Majority (n = 7/8) of the cases were resolved in 3 weeks and all were resolved in 4 weeks. None of the cases required a repeat procedure. No intraoperative or postoperative complication was noted in any case. Conclusion: MiOCT-guided drainage of stromal fluid pockets in cases of corneal hydrops is a safe and effective technique. Real-time monitoring with MiOCT allows for fluid clefts location, instrument depth judgment, and complete drainage of fluid clefts. It is especially useful in cases with severe corneal edema and large fluid clefts where medical management alone fails.